A Bibliometric analysis of physiology and management in China based on three major agronomic journals - Kumar, Dinesh; Singh, Navdeep (International Journal of Psychosocial Rehabilitation, 2021)
The study of rice has long been a main concern in China, and the nation reliably distributes the most papers in insightful diaries regarding the matter, especially in the space of rice reproducing and hereditary qualities. A bibliometric approach was utilized to inspect the examples in papers on rice physiology and the board distributed by Chinese scientists. On September 8, 2017, the Web of Science was looked for three significant agronomic diaries (Agronomy Journal, Crop Science, and Field Crops Research). Since their beginning, Chinese yield physiologists and directors have distributed an aggregate of 186 papers in these three diaries. For the years 1993-2005, 2006-2011, and 2012-2017, the normal number of these papers each year was 1.6, 6.5, and 21.0. Reference execution has additionally worked on altogether throughout the most recent ten years for these creators. The greater part of the 186 papers were distributed by the three driving establishments: Huazhong Agricultural University, Yangzhou University, and Nanjing Agricultural University. Most papers on rice crop psychology and the executives were first or co-authored by Hunan Agricultural University’s Huang Min and Huazhong Agricultural University’s Peng Shaobing. As a result of this, rice crops have been studied extensively for their yield potential and for their ability to efficiently use nitrogen. Studies into the effects of global warming, such as the critical nitrogen dilution curve and high temperature stress on crops, have grown in popularity in recent years. Rice ratooning, yield gap, and simplified and reduced-input practices are all the subject of new research.